Multidrug Resistance in Pasteurellaceae Associated With Bovine Respiratory Disease Mortalities in North America From 2011 to 2016 - Klima, Cassidy L.; Holman, Devin B.; Cook, Shaun R.; Conrad, Cheyenne C.; Ralston, Brenda J.; Allan, Nick; Anholt, R. Michele; Niu, Yan D.; Stanford, Kim; Hannon, Sherry J.; Booker, Calvin W.; McAllister, Tim A. (Frontiers in Microbiology, 2020)
Multidrug-resistant (MDR; resistance to ≥ 3 antimicrobial classes) members of the Pasteurellaceae family may compromise the efficacy of therapies used to prevent and treat bovine respiratory disease (BRD) in feedlot cattle. This study examined the prevalence of multidrug resistance in strains of Mannheimia haemolytica and Pasteurella multocida collected from BRD cattle mortalities in North America. Isolates of M. haemolytica (n = 147) and P. multocida (n = 70) spanning 69 Alberta feedlots from 2011-2017 and two US feedlots from 2011-2012 were examined for antimicrobial resistance (AMR) in association with integrative and conjugative elements (ICEs). Overall, resistance was high in both bacterial species with an increase in the prevalence of MDR isolates between 2011 and 2017. Resistance to >7 antimicrobial drugs occurred in 31% of M. haemolytica, and 83% of P. multocida isolates. Resistance to sulfadimtoxine,, trimethoprim/sulfamethoxazole, neomycin, clindamycin oxytetracycline, spectinomycin, tylosin, tilmicosin, and tulathromycin was most common. Although ˃ 80% of strains harbored three or more ICE-associated genes, only 12% of M. haemolytica and 77% of P. multocida contained all six, reflecting the diversity of ICEs. There was evidence of clonal spread as P. multocida and M. haemolytica isolates with the same pulsed-field gel electrophoresis profile from the US in 2011 were isolated in Alberta in 2015- 2017. This work highlights that MDR strains of Pasteurellaceae containing ICEs are widespread and may be contributing to BRD therapy failure in feedlot cattle. Given the antimicrobial resistance gene profiles identified, these MDR isolates may be selected for by the use of macrolides, tetracyclines, and/or in-feed supplements containing heavy metals.